Investigation of Temperature and Humidity Control System for Mushroom House - Abd Wahab, Hanani; Abdul Manap, Muhamad Zariq Imran; Ismail, Al Emran; Pauline, Ong; Ismon, Maznan; Zainulabidin, Muhd Hafeez; Mat Noor, Fazimah; Mohamad, Zaleha (International Journal of Integrated Engineering, 2019)
Abstract: Monitoring and control the mushroom house environment play an important role in mushroom cultivation quality. Assurance of optimal temperature and humidity has a direct influence on the mushroom growth performance. Traditionally, mushroom cultivation has required a great effort to connect and distribute all the sensors and data acquisition systems. Natural environment such as the temperature during the day either on a hot day and the rain is affecting the temperature and moisture in the mushroom house directly. The optimal temperature and humidity for mushroom house is around 20Â°C and 80% respectively. For this reason, in order to maintain an optimal temperature and humidity, Matlab Simulink was developed to run simulations on the system. Simulink’s block diagram is composed of three main parts for this system whereas input, control system and the output temperature and humidity for the mushroom house. Matlab/Simulink tool is use for modeling, simulating and analyzing the performance of the system.